How farmer trade aid undermines the US in world markets - Glauber, Joseph W. (2019)
U.S. agricultural producers have been hard hit by China, Mexico, Canada and other countries who have imposed tariffs against U.S. agricultural products in retaliation for adverse trade actions taken by the Trump administration against their exports. Agricultural exports to China have fallen from almost $22 billion in fiscal 2017 to $6.5 billion projected for fiscal 2019. Soybeans exports have fallen by about 15 percent in volume, as exporters have sought alternative markets and stocks have grown as a result. A big winner from the tariffs has been Brazil, which has seen its exports to Brazil.